Detection of rare nematode resistance Rhg1 haplotypes in Glycine soja and a novel Rhg1 α‐SNAP. Issue 1 (30th October 2021) - Grunwald, Derrick J.; Zapotocny, Ryan W.; Ozer, Seda; Diers, Brian W.; Bent, Andrew F.
Abstract: This study pursued the hypothesis that wild plant germplasm accessions carrying alleles of interest can be identified using available single nucleotide polymorphism (SNP) genotypes for particular alleles of other (unlinked) genes that contribute to the trait of interest. The soybean cyst nematode (SCN, Heterodera glycines [HG]) resistance locus Rhg1 is widely used in farmed soybean [ Glycine max (L.) Merr.]. The two known resistance‐conferring haplotypes, rhg1‐a and rhg1‐b, typically contain three or seven to 10 tandemly duplicated Rhg1 segments, respectively. Each Rhg1 repeat carries four genes, including Glyma.18G022500, which encodes unusual isoforms of the vesicle‐trafficking chaperone α‐SNAP. Using SoySNP50K data for NSFRAN07 allele presence, we discovered a new Rhg1 haplotype, rhg1‐ds, in six accessions of wild soybean, Glycine soja Siebold & Zucc. (0.5% of the ∼1, 100 G. soja accessions in the USDA collection). The α‐SNAP encoded by rhg1‐ds is unique at an important site of amino acid variation and shares with the rhg1‐a and rhg1‐b α‐SNAP proteins the traits of cytotoxicity and altered N‐ethylmaleimide sensitive factor (NSF) protein interaction. Copy number assays indicate three repeats of rhg1‐ds . G. soja PI 507613 and PI 507623 exhibit resistance to HG type 2.5.7 SCN populations, in part because of contributions from other loci. In a segregating F2 population, rhg1‐b and rhg1‐ds made statistically indistinguishable contributions to resistance to a partially virulent HG type 2.5.7 SCN population. Hence, the unusual multigene copy number variation Rhg1 haplotype was present but rare in ancestral G. soja and was present in accessions that offer multiple traits for SCN resistance breeding. The accessions were initially identified for study based on an unlinked SNP. Core Ideas: Germplasm carrying useful alleles can be identified using SNP data for other genes. Glycine soja accessions with potentially valuable SCN resistance were identified. A novel variant of the Rhg1 α‐SNAP SCN resistance protein was identified and characterized. The unusual Rhg1 multigene copy number variation structure arose prior to the domestication of soybean.